Lifting the Veil: COVID-19 and the Need to Re-consider Airline Regulation - Munari, Francesco (European Papers (www.europeanpapers.eu), 2020)
Based on the assumption that the COVID-19 pandemic might provide the occasion to re-think the role of aircraft passenger transportation, this Insight advocates a re-evaluation of the market models developed over the past decades to deregulate the airline industry. The first aspect on which the Insight focuses is the unfeasibility of a long-term generally subsidized air transport sector under EU law, especially in the aftermath of the COVID-19 pandemic: the likely decrease of both supply and demand casts in doubt the consistency of significant distortions necessarily caused by public subsidies in this sector with EU competition law. Moreover, under environmental law and policy perspectives, the Insight highlights the inconsistencies between the negative externalities of the current air transport policy and the climate goals fostered by the EU. In this vein, the Author underlines that, in lieu of increasing subsidies, an EU transport policy consistent with climate goals should reduce them. This, however, would decrease again the supply of air transportation, in line with the need to reduce the unsustainable levels of emissions of aircrafts. In this scenario, the resulting diminished volume of air transport services is assessed against the rationale originally supporting the deregulation of this sector decided some 30 years ago at EEC level, i.e. the abolition of national monopolies preventing freedom to provide services. In particular, the Author questions whether such a rationale still justifies both the deviations from climate goals and the risk to perpetuate the competitive model in a substantially changed industry. After all, deregulation has led to a substantial concentration in the market but at the same time, as the COVID-19 pandemic shows, a situation of sudden deprivation of the existing transportation network for millions of passengers. And because an airline transportation industry (albeit in more limited size) is essential for industrial policy concerns, the Author proposes thorough reflection in which the coronavirus crisis can be seen as an opportunity for a (modern) re-regulation of this sector.
European Papers - A Journal on Law and Integration, 2020 5(1), 461-467
I. The lockdown of passenger air transport as a response to COVID-19 and the questions it raises to policymakers. - II. Concerns from the competition law viewpoint of State aids to rescue airline companies in a post-emergency scenario. - III. Environmental concerns and air transport policy: a sharp decrease in the offer of air passengers' services should be considered. - IV. Freedom of market access in the passenger air transport industry: negative economic externalities and the need to rethink mobility of persons vis-à-vis other values and priorities. - V. A brief history of de-regulation of the airline industry in the EU: what's left after more than three decades. - VI. Will the pandemic be able to lift the veil from our eyes? - VII. Industrial policy concerns for the future of air transport. - VIII. "Back to the future": regulating the aviation industry to cope with market failures, environmental goals and industrial policy needs. - IX. Concluding remarks: COVID-19 as a "didactic momentum".
European Forum Insight of 28 May 2020
Keywords: COVID-19 and the EU; State aids; air transport; environmental protection; market regulation; industrial policy